2019
DOI: 10.1186/s12885-018-5222-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of genistein suppresses hepatocellular carcinoma through AMPK-mediated apoptosis and anti-inflammation

Abstract: BackgroundWomen have a lower risk of hepatocellular carcinoma (HCC) than men, and the decreased possibility of HCC in women is thought to depend on estrogen levels. As a soybean-isoflavone product, genistein has estrogenic activity in various reproductive tissues, because it mimics 17β-estradiol and binds the estrogen receptor. Though genistein is a known liver cancer suppressor, its effects have not been studies in long-term experiment, where genistein is fed to a female animal model of HCC.MethodsMice were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 43 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…Hence, the significant AMPK determinants activity are conformational switch induced by AMP and the α subunit phosphorylation on Thr172 (Figure 1). A series of reviews have reported the downstream signal pathways involving AMPK activity such as mitochondrial biogenesis, autophagy and inflammation response, as well summarized in other reviews [25,31,32]. Some downstream signal pathways of AMPK are shown in Figure 1.…”
Section: Structure and The Activation Of Ampkmentioning
confidence: 99%
“…Hence, the significant AMPK determinants activity are conformational switch induced by AMP and the α subunit phosphorylation on Thr172 (Figure 1). A series of reviews have reported the downstream signal pathways involving AMPK activity such as mitochondrial biogenesis, autophagy and inflammation response, as well summarized in other reviews [25,31,32]. Some downstream signal pathways of AMPK are shown in Figure 1.…”
Section: Structure and The Activation Of Ampkmentioning
confidence: 99%
“…It has also been postulated that genistein enhanced the phosphorylation and activation of p53, while decreased the ratio of Bcl-2/Bax and Bcl-xL/Bax and the level of phosphorylated Akt (also known as protein kinase B), which result in cells undergoing apoptosis (Ouyang et al, 2009). Genistein-mediated activated protein kinase (AMPK) upregulation increased apoptosis of hepatocytes, in hepatocellular carcinoma (HCC) through energy-dependent caspase pathway (Lee et al, 2019). In Hep3B cells, genistein activated AMPK, which promoted apoptosis accompanied by downregulation of the proinflammatory responses and increasing mitochondrial respiration.…”
Section: Molecular Mechanisms Of Action Of Genisteinmentioning
confidence: 99%
“…29 Suppression of the pro-inflammatory response by KCs could inhibit the initiation of HCC but could promote the progression of HCC. 30 As determined by Lee et al, 30 in accordance with enhanced inflammation, there were significant increases in hepatic inflammation, fibrosis and tumor growth in mice fed a high-fat diet, which might be attributed to the pro-inflammatory, profibrogenic and pro-tumoral responses mediated by vascular endothelial growth factor-dependent angiogenesis of KCs. 31 It is therefore inferred that liver macrophage phenotypes are not fixed and that their dynamic alterations are implicated in hepatocarcinogenesis and its progression.…”
Section: Functional Characterization Of M2 Tams In Hccmentioning
confidence: 79%